Approaching the legal framework Free Investment Institutions in Spain (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
The present paper studies the legal framework of Hedge Funds in Spain. The study developes the different regulations in European countries, the EU, the United Kingdom and the United States of America. It also describes the structure of Hedge Funds in Spain, as well as outside It continues with the legal Spanish regulation about the distribution of Hedge Funds, and with the guidelines of the investor’s protection. The paper concludes with the “Closed Investment Vehicles”, a way to make distribution of Hedge Funds, which is regulated by Spanish “Issues Act” (Decreto deEmisiones).
Keywords: Hedge Funds; UCITS “high-risk-investment UCITS; investor’s protection; “closed UCITS”; alternative investment management; prime broker; qualified invertors; regulatory framework of Hedge Funds; Fund vehicles